Dynamic Voluntary Contribution to a Public Project - Leslie M. Marx; Steven A. Matthews (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1997)
We consider the dynamic private provision of funds to a project that generates a flow of public benefits. Examples include fund drives for public television or university buildings. The games we study have complete information about payoffs, allow each player to contribute each period, and let each player observe only the aggregate of the other players' past contributions. The symmetric Nash equilibrium outcomes are characterized and shown to be also perfect Bayesian equilibrium outcomes. If the number of periods in which contributions are accepted is large enough, and the players are patient or the period length is short enough, equilibria exist in which the project is eventually or asymptotically completed. Some equilibria with these features are Markov perfect. In some, the time to completion shrinks to zero with the period length–free riding vanishes in the limit. These results are in contrast to those of other models in which allowing repetitive contributions worsens the free riding problem.
Keywords: 330